The Influence of Experience and Trust on Loyalty, with Satisfaction as a Mediator - Dominico Nixon Verdy Rajendra; Endang Tjahjaningsih (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to analyze and describe the influence of experience and trust on loyalty mediated by user satisfaction of the Shopee application in Surakarta. This type of research is causal associative, namely research conducted with a quantitative approach with primary data. The sampling technique used is non-probability sampling in the form of purposive sampling obtained by a total of 100 respondents. The data collection technique uses a questionnaire with a seven-point Likert scale. Data analysis uses instrument tests consisting of validity and reliability tests, model tests consisting of determination coefficient tests, multiple linear regression analysis tests with t-tests, and Sobel tests using the SPSS application. The results show that experience has a positive and significant effect on satisfaction. Trust has a positive and significant effect on satisfaction. Experience has a positive and significant effect on loyalty. Trust has a positive and significant effect on loyalty. Satisfaction has a positive and significant effect on loyalty. Satisfaction is proven to be able to mediate the influence of experience and trust on loyalty.